Not on a white horse - Springer, Nancy (New York : Distributed by Random House, 1988)
From the day twelve-year-old Rhiannon spots a lost white Arabian gelding in the woods near her small Pennsylvania mining town, her life finds a focus as she learns to deal with family problems and decides the direction her life will take.
"A Bullseye book.".
Booklist.
Horn Book.
School Library Journal.
6.7
6.7
Keywords: Family problems -- Fiction; Horses -- Fiction; Family problems -- Fiction; Horses -- Fiction